PHARMACEUTICAL STANDARDIZATION OF CHITRAKADI GHRITA - Subbalakshmi, Bhaskaruni; Paranjape, Meera Madhukar (International Journal of Ayurveda and Pharma Research, 2015)
Ghrita (ghee) preparation is superior among all the Sneha dravyas because of its power to assimilate effectively the properties of the substances. Chitrakadi Ghrita, a polyherbal formulation is suggested in the management of Vandhyatva (Infertility) caused by Yonidosha mentioned by Acarya Sushruta in Sushruta Samhita. Physico-chemical analysis of the coarse powder made out of the crude drugs and final preparation i.e., Chitrakadi Ghrita was carried out in the Indian Institute of Chemical Technology (IICT), Hyderabad, A.P. Qualitative analysis was done to identify the compounds Triterpnoids, Steroids, Flavonoids, Phenolic compounds, Carbohydrates got positive results in raw herbal powder and Chitrakadi ghritam. Chitrakadi ghritam shows Acid value was 4.78, Saponification value 280.5, Refractive Index value 1.53, Iodine value 28.7, Specific gravity was 0.9, Ester Value 275.72, Bulk density value 1.60, Peroxide value 9.22. Scanning Electron Microscope (SEM) with Energy Dispersive X-ray analysis (EDX) shows no heavy metals in Chitrakadi Ghrita. TLC was carried out both ChG and HPChG after organizing appropriate solvent system in which TLC examination revealed that it is a complex mixture of 10 to 12 compounds having close Rf values respectively. The present study provided to demonstrate applicability of the methods to standardization of Chitrakadi ghrita, the analysis report shows the values are within the limits, and there is no harmful metals found. The normal limit of Microbial contamination was estimated. It does not contain any harmful microbes such as Escherichia coli, Salmonella spp., Pseduomonas aeruginosa, Staphylococcus aureus. Chitrakadi ghrita can be given internally to the patients for the management of Vandhyatva (Infertility).